2014
DOI: 10.1111/eos.12134
|View full text |Cite
|
Sign up to set email alerts
|

Inlay‐retained cantilever fixed dental prostheses to substitute a single premolar: impact of zirconia framework design after dynamic loading

Abstract: The purpose of this in-vitro study was to evaluate the influence of the framework design on the durability of inlay-retained cantilever fixed dental prostheses (IR-FDPs), made from zirconia ceramic, after artificial ageing. Forty-eight caries-free human premolars were prepared as abutments for all-ceramic cantilevered IR-FDPs using six framework designs: occlusal-distal (OD) inlay, OD inlay with an oral retainer wing, OD inlay with two retainer wings, mesial-occlusal-distal (MOD) inlay, MOD inlay with an oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…However, clinical recommendation is limited because of the in vitro nature of the test design with isolated loading on the distal aspect of the cantilever extensions. The lever defined by the loading point with a distance of 3.5 mm to the adjacent abutment tooth simulated a centric contact point and was recommended to reduce adverse loading . The conclusions are strongly limited to our load application design which eliminates loading at a more distal point or any eccentric contact.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical recommendation is limited because of the in vitro nature of the test design with isolated loading on the distal aspect of the cantilever extensions. The lever defined by the loading point with a distance of 3.5 mm to the adjacent abutment tooth simulated a centric contact point and was recommended to reduce adverse loading . The conclusions are strongly limited to our load application design which eliminates loading at a more distal point or any eccentric contact.…”
Section: Discussionmentioning
confidence: 99%
“…Vollkeramische Adhäsivbrücken zum Ersatz von Eck-und Seitenzähnen wendet der Autor seit mehr als 10 Jahren erfolgreich in solchen Einzelfällen an, in denen Implantate nicht oder nur mit unverhältnismäßig großem Aufwand möglich sind, oder wenn Patienten eine Implantation ablehnen. Da für diese Anwendung bisher nur vorläufige wissenschaftliche Daten existieren [31][32][33][34], werden die Patienten explizit darüber aufgeklärt, dass der Einsatz von einflügeligen vollkeramischen Adhäsivbrücken zum Ersatz von nicht angelegten Prämolaren und Eckzähnen noch als quasi experimentell anzusehen ist. Die hauptsächlichen Risiken bestehen im Retentionsverlust oder der Fraktur der einflügeligen Adhäsivbrücke.…”
Section: Vergleich Der Therapie-optionenunclassified
“…In much of the research to date, reports have indicated that the mechanical properties of zirconia are equal to or superior to those of metal. However, if we consider the device's function as a long-term prosthetic device under mastication, it is essential to measure its fracture strength, while taking into consideration its clinical form and the unfavorable intraoral environment [10][11][12][13] . Previous studies have analyzed occlusal contact damage-associated fracture behavior for zirconia crowns 14) and have demonstrated the utility of supportive designs and supportive regions in frame designs when loads are applied to the occlusal surface at various points 15) .…”
Section: Introductionmentioning
confidence: 99%